The Growth Responses of Shallot (Allium cepa L.) Toward Different Levels of Salt Stress - Kurniawan, Andi; Noviandi, Widi Dwi; Rahmandhias, Deris Trian (Akta Agrosia, 2024)
Shallot (Allium cepa L.) is an annual Liliaceae family plant and a major horticultural commodity globally. As a crucial horticultural product, market demand for shallots tends to increase. However, global climate change causes saline land areas to increase. Salt stress is one of the leading challenges limiting yield worldwide. This study aims to understand the impact of salt stress on the growth of shallots and their stress tolerance limits. This research was conducted from August to October 2023 in Wonorejo Village, Poncokusumo District, Malang Regency. The plant material used in this study was the Tajuk variety of shallots. This study used a Randomized Block Design (RBD) with four salinity treatments ( 0, 100, 150, and 200 mM NaCl), each replicated three times. Variables observed in this study include plant length, leaf number hill-1, tiller number hill-1, and plant fresh weight hill-1 that were observed at 2, 4, 6, and 8 weeks after planting (WAP). Our results showed that plants treated with 100 mM NaCl decreased plant length, leaves number, tiller number, and plant fresh weight (shoots, roots, and bulbs) by 8 %, 10 %, 8 %, and 12 %, respectively. While at a concentration of 150 mM, the reduction was 14 %, 30 %, 18 %, and 22 %. Furthermore, the highest percentages of decrease of those growth variables, up to 27 %, 42 %, 31 %, and 41 %, respectively, were obtained at 200 mM treatment. These findings may help to understand the morphological and ecological aspects of salt stress in plants and how plants grow and develop under salinity conditions. This study also highlights the importance of further studies on the physiological of shallot on salt stress. This might result in innovative strategies and technology that crops' resilience to salinity, and ensure food security and the sustainability of farming in impacted areas Keywords: shallot, abiotic stress, salinity, plant growth.